1990
DOI: 10.1128/jb.172.8.4549-4554.1990
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Rhodobacter capsulatus mutants defective in oxygen regulation of the puf operon

Abstract: cis-acting mutations that affect regulation of the Rhodobacter capsulatus puf operon by oxygen were isolated by placing the mutagenized puf regulatory region 5' to a promoterless Tn5 neo gene, which encodes resistance to kanamycin (Kmi). R. capsulatus mutants that failed to show wild-type repression of KM' by oxygen were selected and analyzed. Four independent clones contained point mutations, three of which were identical, in a region of dyad symmetry located between puf operon nucleotide positions 177 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 40 publications
(31 reference statements)
1
18
0
Order By: Relevance
“…Mutational analysis of the puf promoter region has indicated that this promoter may be under control of a repressor, as evidenced by increased aerobic expression of some promoter point mutations (18). There has also been a report of an uncharacterized protein that binds to the puf operon promoter in an oxygen-dependent manner (13,14,15).…”
Section: Discussionmentioning
confidence: 98%
“…Mutational analysis of the puf promoter region has indicated that this promoter may be under control of a repressor, as evidenced by increased aerobic expression of some promoter point mutations (18). There has also been a report of an uncharacterized protein that binds to the puf operon promoter in an oxygen-dependent manner (13,14,15).…”
Section: Discussionmentioning
confidence: 98%
“…Vitreoscilla was routinely grown in PYA medium (1% peptone, 1% yeast extract, and 0.02% sodium acetate, pH 7.8) at 25°C. E. coli strains were grown in Luria Broth (1% tryptone, 0.5% yeast extract, and 1% NaCl, pH 7.5) at 37°C, and the oxygen level was adjusted according to the method adopted by Narro et al (28) and as described previously (29). The plasmid, Bluescript KS(ϩ), was obtained from Stratagene and the expression-secretion vector, pTMNO (30), was used for the generation of the ompA-vgb gene fusion.…”
Section: Methodsmentioning
confidence: 99%
“…1). The pMLN plasmids carry the RK2 replicon, and their construction has been described previously (16). The base pair exchange in the puf upstream region present in plasmid pMLN44 is indicated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The arrow above the puf sequence points to the C nucleotide that is changed to a T in pMLN44. The arrows below the puf DNA sequence indicate a dyad symmetry involved in the oxygen regulation of puftranscription (16). The numbering of the puf sequence is with respect to the transcriptional start, which is 0.…”
mentioning
confidence: 99%